MASS MEDIA IN TEACHING ENGLISH - Manasbayeva, N.Sh. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article aims at analyzing the importance of using Mass Media in the classroom and finding the ways how to use Printed and Audio-visual Media. This article is based not only on the literature review but also on personal experience. It is a brief description of some practical examples and some tips for novice teachers. Furthermore, this article tends to deal with some of the key issues of using media in the classroom. The following issues are open for discussion: the importance of Media in general and in education in particular; newspapers, magazines, radio, television and internet in the classroom, etc.
Keywords: teaching English; multimedia in education; mass-media in education; new technologies in teaching English